Appointing judges in an age of judicial power : critical perspectives from around the world - Russell, Peter H.; Malleson, Kate (University of Toronto Press, 2006)
The global expansion in judicial power has led to a growing interest in the way judges are chosen. Reform of the judicial selection process is on the political agenda in many countries but the nature of that process differs according to the type of process used - whether a career judiciary, an elected judiciary (direct and indirect), appointment by the executive, or a hybrid system. The main aim of this volume is to analyse common issues arising from increasing judicial power in the context of different political and legal systems, including those in North America, Africa, Europe, Australia, and Asia. The contributors seek to assess the strengths and weaknesses of structural and procedural reforms being proposed or implemented. Particularly important issues include the growing pressure to rethink the balance between judicial independence and accountability and the growing recognition of the importance of selecting judiciaries with a greater diversity in composition. Edited by Kate Malleson and Peter H. Russell, the volume marks the first time an analysis of judicial selection in such a wide range of different systems has been undertaken. It will interest anyone concerned with the global shift of political power toward the judiciary. Contributors:Jim AllenSufian Hemed BukururaLeny De GrootFrancois du BoisAntoine GaraponMahmoud HamadElizabeth HandsleyColin HawesChristine LandfriedRuth MackenzieKate MallesonDerek MatyszakvTed MortonDavid O'BrienAlan PatersonMarie ProvinePeter H. RussellEli SalzbergerPhillipe SandsMichael TolleyAlexei TrochevMary Volcansek.